Open or Closed? - Tala, Kassm; Dylan, Freeman (International Journal of Glaucoma, 2020)
A brief educational piece clarifies open‑angle versus angle‑closure glaucoma mechanisms, risk factors, and screening considerations. It provides practical pointers for early detection and referral.
Keywords: silicone oil; ahmed tube shunt; clog tube